2021
DOI: 10.1177/0300060521993318
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of erectile dysfunction and its associated factors among patients with diabetes in Ethiopia: a systematic review and meta-analysis

Abstract: Objectives We aimed to estimate the pooled prevalence of erectile dysfunction (ED) among patients with diabetes mellitus (DM) in Ethiopia and to identify its associated factors. Methods We performed a systematic search of scientific databases (PubMed, ScienceDirect); the grey literature was also searched (Google, Google Scholar). Data were extracted from primary studies using a data extraction format and exported for statistical analysis. I2 tests were used to assess the heterogeneity of studies. Owing to hete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…The prevalence of ED in males with DM varies in different populations and areas. In the systematic review and meta-analysis by Weldesenbet AB et al, the pooled prevalence of ED among patients with DM in Ethiopia was 54.3% (95% CI: 28.2-80.5%) [27]. In the meta-analysis by Kouidrat Y et al, 145 studies were included representing 88,577 males with DM around the world, and they found that the prevalence of ED in males with ED was 52.5% (95% CI, 48.8-56.2%) [28].…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of ED in males with DM varies in different populations and areas. In the systematic review and meta-analysis by Weldesenbet AB et al, the pooled prevalence of ED among patients with DM in Ethiopia was 54.3% (95% CI: 28.2-80.5%) [27]. In the meta-analysis by Kouidrat Y et al, 145 studies were included representing 88,577 males with DM around the world, and they found that the prevalence of ED in males with ED was 52.5% (95% CI, 48.8-56.2%) [28].…”
Section: Discussionmentioning
confidence: 99%
“…ED was an IIEF-5 score ≤ 20. It was labelled mild (score [16][17][18][19][20], moderate (score [11][12][13][14][15], severe (score 5-10) or uninterpretable (score < 5) [19].…”
Section: Data Collection Proceduresmentioning
confidence: 99%
“…Studies in sub-Saharan Africa estimated the prevalence of erectile dysfunction to amount to 24% in the general population and up to 54.3% among diabetic patients [11][12][13]. Population aging and, among diabetic patients, physical inactivity and comorbities appear to be the main factors associated with ED condition.…”
Section: Introductionmentioning
confidence: 99%
“…In Africa, its general prevalence among patients with DM was 71.45% ( 22 ). Different studies on the prevalence of ED among patients with DM in some parts Ethiopia were carried out, and the prevalence was from 6.8% to 85.5% ( 8 , 11 , 19 , 21 , 23 25 ).…”
Section: Introductionmentioning
confidence: 99%